Electrochemical Oxidation of d‐Glucose in Alkaline Medium: Impact of Oxidation Potential and Chemical Side Reactions on the Selectivity to d‐Gluconic and d‐Glucaric Acid. Issue 1 (4th November 2019) - Moggia, Giulia; Kenis, Thomas; Daems, Nick; Breugelmans, Tom
Abstract: The electrocatalytic oxidation of d ‐glucose was studied in alkaline medium on copper, platinum, and gold electrodes with particular emphasis on the synthesis of a high value‐added product: glucaric acid. An initial ranking of the three different materials, with respect to their electrochemical activity towards glucose oxidation, was performed utilizing cyclic voltammetry. To determine which functional group can react on which metal, cyclic voltammetry experiments were performed in three different solutions containing 0.04 M gluconic acid, glucuronic acid, or glucaric acid in 0.1 M aqueous NaOH. The observations drawn based on these initial experiments were then verified by analyzing the product solutions (obtained after prolonged electrolysis experiments) with HPLC analysis. The oxidation of glucose on copper at high potentials leads predominantly to C−C cleavage products, mainly formic acid, with a selectivity of 54.2 %; whereas, at lower potentials, the oxidation of the aldehyde group on C1 and of the hydroxymethyl group on C6 produces moderate yields of gluconic and glucaric acid. On platinum, the oxidation of the aldehyde group on C1 is the most relevant process; therefore, the selectivity towards gluconic acid obtained is as high as 78.4 %. Nevertheless, at lower potentials, a higher selectivity to glucaric acid (12.6 %) and a lower selectivity to gluconic acid (68.0 %) are the result of a more effective oxidation of also the hydroxymethyl group on C6. Gold is the most active and selective electrocatalyst of the ones examined in this work. On gold, at lower potentials, the oxidation of the aldehyde group on C1 produces 86.6 % of selectivity to gluconic acid while, at higher potentials, the oxidation of the hydroxymethyl group on C6 also takes place, promoting the further oxidation to glucaric acid (13.5 % of selectivity is reached after 65 h of reaction at 5 °C, with a residual gluconic acid equal to 65.8 %). The demonstrated dependence of the selectivity on the oxidation potential suggests new future perspectives for the electrocatalytic oxidation of d ‐glucose to d ‐glucaric acid on bare metal electrodes. Moreover, the low selectivity of this process, very often claimed in literature, has been ascribed here for the first time to two chemical processes, which are in competition with the electrochemical one and both consume the reactant and promote the formation of undesired side‐products. Abstract : Choosing wisely : A two‐compartment glass cell separated by a cation‐exchange membrane is employed in batch mode for the electrochemical oxidation of d ‐glucose in alkaline media. Three electrode materials (copper, platinum, and gold) are examined with respect to their selectivity towards d ‐gluconic and d ‐glucaric acid. A strong dependence of the electro‐reactivity of the two terminal functional groups of d ‐glucose on the oxidation potential is demonstrated to be key for the control of the selectivity to the products of interest.